2013
DOI: 10.1111/fwb.12161
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐B‐driven pigmentation and genetic diversity of benthic macroinvertebrates from high‐altitude Andean streams

Abstract: 1. Photoprotective pigments in benthic macroinvertebrates may reduce the damage caused by the blistering UV-B radiation in Andean high-altitude streams above 3500 m. The aim of this study was therefore to determine whether melanisation in macroinvertebrates inhabiting high-altitude Andean streams is an adaptive response to high UV-B radiation. To explore whether altitude-related differences in melanin concentration between taxa were due to a variable community composition or due to population differentiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Rautio & Korhola ; Loayza‐Muro et al . ; Bastide et al . ), but few have experimentally shown an increased cuticular melanin deposition as a plastic response to UV radiation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rautio & Korhola ; Loayza‐Muro et al . ; Bastide et al . ), but few have experimentally shown an increased cuticular melanin deposition as a plastic response to UV radiation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several correlational studies reported the connection between cuticular melanin and UV radiation (e.g. Rautio & Korhola 2002;Loayza-Muro et al 2013;Bastide et al 2014), but few have experimentally shown an increased cuticular melanin deposition as a plastic response to UV radiation (e.g. Belden & Blaustein 2002;Loayza-Muro et al 2012;Ahlgren et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ephemeroptera and most other non‐Diptera insect taxa in tropical Andean streams are typically rare at closer distances to glaciers (Jacobsen et al ., ), potentially due to low‐oxygen and/or high‐UV conditions near these extremely high‐altitude glacier sources in the tropics (compared to glacier‐fed streams that have been studied in the temperate zone; e.g. Jacobsen & Brodersen, ; Loayza‐Muro et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In particular it was recently demonstrated the ability of Chironomids to perform melanin synthesis, giving higher tolerance to toxic metals (Loayza-Muro et al, 2013), it is of particular interest in considering the interference of tricyclazole with melanin synthesis (Kunova et al, 2013), this requires further study but can be a basis to explain a tolerance of some benthic macroinvertebrates to tricyclazole toxicity. …”
Section: Discussionmentioning
confidence: 99%